Die sinodale verband van die Nederduitse Gereformeerde Kerk in die Vrystaat: enkele tendense by die ontstaan daarvan in 1864-1865 - Strauss, P. J. (Faculty of Theology, University of the Free State, 2007)
In the Reformed tradition the basic documents of a church, apart from the Bible on which it should be based, are its confessions of faith and its church order.These documents show tendencies which indicate the orientation point and belief of such a church.If one investigates the way in which the Dutch Reformed Church in the Free State approached its confessions and church order at the church conference in 1864 where it was founded, and at its first Synod in 1865, three points emerge.Firstly this Synod was historically close to the Dutch Reformed Church in the Cape;secondly it was Reformed in its government, but mixed it with elements of collegialism;and thirdly it was focused on the Orange Free State, the country in which it originated. Elements of the same approach can still be seen in this synod today.It still wants to be Reformed;it still has a stability and tendency not to be radical — it very often stays in calm waters — and it can be convinced of the merit of an issue if it can be shown that it corresponds to the Scriptures and the confessions.Apart from that, there are indications that it clearly sees itself as a synod in the Free State Province.
Keywords: DR Church in the Free State; Origin; Church history; Church polity